Pengaruh Pengeluaran Pemerintah untuk Pendidikan, Kesehatan, dan Infrastruktur terhadap PDRB dan Penyerapan Tenaga Kerja di Propinsi Jawa Barat Tahun 2012 - Nalyda Yola Althofia; Neli Agustina (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
Labor is part of the population that is capable of doing the work to produce goods and services. Therefore, workers need to be empowered optimally in order to drive the economic process. According to Keynes, one of the efforts that can be done is fiscal policy by increasing government spending leading to a reduction in unemployment. However, in West Java this expectation was not realized. West Java has a large government spending, but its labor absorption is not high. It is shown from the percentage of the working population of the labor force in West Java in 2012 remained below national. This study determines the effect of government education, health and infrastructure expenditures on economic growth and employment in West Java. The recursive equation mode is employed, showing that education and infrastructure spending have positive effect on economic growth and employment. Health expenditure prove to be insignificant. In addition,in West Java, economic growth has positive effect on employment.